HUBUNGAN KELINCAHAN DENGAN KETERAMPILAN DRIBBLING BOLA BASKET ACADEMY JAYADEWATA BUCKETLIST KOTA BOGOR - Juan Alvin Pardede, Samuel; Akbar Izzuddin, Deden; Kinanti Dewi, R. Retna; Armen Gemael, Qorry; Aulia, Dany (Indonesia Sport Journal, 2025)
In various regions, basketball clubs and training academies are increasingly emerging to produce talented young athletes. However, despite the growing popularity of basketball, the challenges in coaching are still quite complex. One of the main problems is the imbalance in the quality of coaching between areas that have adequate infrastructure and areas that still lack facilities. In addition, the coaching system in Indonesia still faces challenges in terms of the continuity of the coaching level from early childhood to professional level. Although there are programs such as the Student League (LIMA) and Developmental Basketball League (DBL) that provide a platform for young players to compete, the transition from junior to professional level is still not optimal